Kdo je Begunka pri zibeli? - Šter, Katarina (Muzikološki zbornik, 2018)
The present article opens some new questions about Begunka pri zibeli The Refugee by the Cradle, one of Anton Lajovic's best and most expressive songs for voice and piano, which was also connected with the historical events by the Soča/Isonzo front in the First World War. Special attention is given to the original literary text by Oton Župančič. His allusions to the painting of the Virgin Mary from the place of pilgrimage Sveta gora near Gorica/Gorizia, which also shared the refugee's fate, could bring new insights into the identity of the "refugee by the cradle".
Keywords: Lajovic, Anton; samospev; slovenska glasba; slovenska poezija; slovenski skladatelji; Sveta gora pri Gorici; svetovna vojna 1914-1918; Župančič, Oton